Biological activities and major components determination in essential oils intended for a biodegradable food packaging - Ribeiro-Santos, R. (2021)
Since ancient times, aromatic plants have been used in food and in folk medicine. Currently, essential oils and their compounds are attracting great interest due to their proven action to preserve food quality, to extend foodś shelf-life and due to be natural. Essential oils from Ocimum basilicum (basil), Cinnamomun cassia (cinnamon), Cinnamomun zeylanicum (cinnamon) and Rosmarinus officinalis (rosemary) were analyzed by Gas Chromatography coupled with Flame Ionization Detector and with Mass Spectroscopy and by Ultra High Performance Liquid Chromatography with a Diode Array Detector. The antimicrobial activity against Escherichia coli, Staphylococcus aureus and Penicillium spp and antioxidant activities by FRAP, DPPHradical dot, ABTSradical dot+ and β-carotene bleaching assays were evaluated. C. cassia essential oils presented a strong antimicrobial activity, with a range of minimum inhibitory concentrations between 0.04–0.07 mg mL−1, depending on the microorganism tested. The main compound of C. cassia essential oil, cinnamaldehyde, showed antimicrobial effectiveness. In general, C. zeylanicum essential oil and its major compound, eugenol, presented the highest antioxidant activity. Ultra High Performance Liquid Chromatography confirmed the results of the essential oils main constituents, analyzed firstly by Gas Chromatography. Ultra High Performance Liquid Chromatography technique showed to be a valuable alternative tool for the identification and quantification of the major compounds of essential oils, especially when these are incorporated into food packaging and there is the need of carrying out migration studies in food or food simulants. Cinnamon essential oils exhibited the highest biological activity directly related to its major compounds, eugenol and cinnamaldehyde. Essential oils showed to have high antioxidant and antimicrobial activity and therefore, they have great potential as natural additives of food packaging.